Analisis Novel “Satu Per Tiga” Karya Ryandi Rachman dengan Pendekatan Ekspresif - Eni Lastiarmahita Sihombing (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the novel Satu Per Tiga by Ryandi Rachman using an expressive approach. This approach views literary works as reflections of the author's inner expression, experiences, and life perspectives. The method used in this study is a qualitative method with descriptive analysis techniques. The research data consists of text excerpts from the novel that contain elements of the author's expression, such as themes, characters, language style, and symbols. The results of the analysis show that the novel Satu Per Tiga represents themes of self-fragmentation, the search for life's meaning, as well as strong values of friendship and independence. The characters in the novel are depicted with psychological complexity that reflects human emotional struggles. The simple, casual, and reflective language style reinforces the impression that this novel is an outpouring of the author's personal expression. Thus, the expressive approach helps readers understand the close relationship between the literary work